Associations between macular retinal vasculature and severity of idiopathic epiretinal membrane - Yun Hsia; Yi-Ting Hsieh (BMC Ophthalmology, 2023)
Abstract Background To demonstrate the associations between the morphology of macular retinal vasculature and disease severity of idiopathic epiretinal membrane (ERM). Methods Macular structures were assessed using optical coherence tomography (OCT), and were classified as “with pseudohole” or “without pseudohole”. The 3 × 3 mm macular OCT angiography images were analyzed using the Fiji software to obtain the vessel density, skeleton density, average vessel diameter, vessel tortuosity, fractal dimension, and foveal avascular zone (FAZ)-related parameters. The correlations between these parameters and ERM grading as well as visual acuity were analyzed. Results For ERM with or without a pseudohole, increased average vessel diameter, decreased skeleton density, and decreased vessel tortuosity were all associated with inner retinal folding and thickened inner nuclear layer, indicating more severe ERM. In 191 eyes without a pseudohole, the average vessel diameter increased, fractal dimension decreased and vessel tortuosity decreased with increasing ERM severity. The FAZ was not associated with ERM severity. Decreased skeleton density (r = -0.37), vessel tortuosity (r = -0.35), and increased average vessel diameter (r = 0.42) were correlated with worse visual acuity (All P < 0.001). In 58 eyes with pseudoholes, a larger FAZ was associated with a smaller average vessel diameter (r = -0.43, P = 0.015), higher skeleton density (r = 0.49, P < 0.001), and vessel tortuosity (r = 0.32, P = 0.015). However, none of the retinal vasculature parameters correlated with visual acuity and central foveal thickness. Conclusion Increased average vessel diameter, decreased skeleton density, decreased fractal dimension and decreased vessel tortuosity were good indicators of ERM severity and associated visual impairment.